2003
DOI: 10.1046/j.1423-0410.2003.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Will it ever be possible to balance the risk of intracranial haemorrhage in fetal or neonatal alloimmune thrombocytopenia against the risk of treatment strategies to prevent it?

Abstract: The number of eligible publications on ICH in untreated FNAIT pregnancies is strikingly limited. The recurrence rate is high. As sufficient data on successive FNAIT cases without ICH are lacking, the occurrence of ICH in pregnancies with thrombocytopenia, but without ICH in a previous sibling, cannot be predicted. We estimate this risk to be 7%. This risk must be balanced against the risk of interventions in treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 67 publications
1
90
1
2
Order By: Relevance
“…The same trend was found in another review study, in which only 15% of in utero ICH cases occurred before 24 weeks [28]. We have identified 16 cases of ICH reported in the literature, where the bleeding was diagnosed in utero and the gestational age at the time of diagnosis was stated.…”
Section: Perspectivesupporting
confidence: 78%
See 2 more Smart Citations
“…The same trend was found in another review study, in which only 15% of in utero ICH cases occurred before 24 weeks [28]. We have identified 16 cases of ICH reported in the literature, where the bleeding was diagnosed in utero and the gestational age at the time of diagnosis was stated.…”
Section: Perspectivesupporting
confidence: 78%
“…In one review of retrospective FNAIT studies and case reports, 81% of ICH cases were detected antenatally [5] while another literature review found that 51% of ICH cases occurred in utero [28]. In this last review, in utero ICH cases were mainly diagnosed after 30 weeks gestation, and only 14% were detected before 20 weeks of gestation…”
Section: Occurrence Of Intracranial Hemorrhagementioning
confidence: 95%
See 1 more Smart Citation
“…13,14 However, true natural history information is lacking. Our previous review on screening studies performed in pregnant women at risk for FNAIT 5 showed that screen-positive cases and those already known to have alloantibodies against fetal platelets received, understandably, various types of interventions.…”
Section: Perinatal Mortality and Neonatal Morbiditymentioning
confidence: 99%
“…La probabilidad de recurrencia de la TFNA en las siguientes gestaciones es muy elevada (hasta el 79%), sobre todo si en la gestación anterior se produjo HIC 13 . Este riesgo puede descender hasta un 7% si la historia de TFNA no estuvo acompañada de HIC.…”
Section: Discussionunclassified